Misdiagnosis-Driven Dental Extractions in Patients with Trigeminal Neuralgia: A Retrospective Study - Hassan AF; Al Sheakh A; Badran SA; Mahmood AA; Alhamdani FY (Journal of Multidisciplinary Healthcare)
Ahmad Fliah Hassan,1 Ali Al Sheakh,2 Saif Anmar Badran,3 Athraa Ali Mahmood,4 Faaiz Yaqub Alhamdani5 1Oral Medicine Department, College of Dentistry, Mustansiriyah University, Baghdad, Iraq; 2Dentistry Department, Al-Yarmouk University College, Baghdad, Diyala, 32001, Iraq; 3Department of Surgery, College of Medicine, Ibn Sina University of Medical and Pharmaceutical Sciences, Baghdad, Iraq; 4Department of Periodontology and Oral Surgery, College of Dentistry, Mustansiriyah University, Baghdad, Iraq; 5Oral and Maxillofacial Surgery and Oral Diagnostics Department, College of Dentistry, Ibn Sina University of Medical and Pharmaceutical Sciences, Baghdad, IraqCorrespondence: Athraa Ali Mahmood, Department of Periodontology, College of Dentistry, Mustansiriyah University, Baghdad, Iraq, Email athrauali@gmail.com, athraa.a.mahmood@uomustansiriyah.edu.iqBackground: Dental extraction is an invasive dental procedure. It should not be considered unless indications apply purpose. However, many trigeminal neuralgia (TN) cases have been treated with dental procedures including dental extraction.Objective: To investigate the frequency of dental extractions for trigeminal neuralgia patients. The objectives of the study were to determine the frequency of dental extractions performed due to the misdiagnosis of trigeminal neuralgia and to assess the role of both dentists and patients in the extraction decision-making process.Materials and Methods: This retrospective study analyzed data from 104 TN patients treated at a neurosurgical hospital between January 2020 and September 2023. One hundred and eight patients were admitted to the Hospital for the management of TN. Patients’ data were collected including biographic data, previous treatments, and the patient’s response to dental treatment provided.Results: Out of 104 treated cases with TN, 88 patients were initially misdiagnosed and treated by dentists for dental pain. Among these patients, fifty-five patients were treated with dental extraction. Thirty-two were females, and 23 patients were males. The highest reported cases were found in the single tooth extraction category (27.3%) of the cases. The frequency of cases with multiple extractions decreases with the increase in the number of extracted teeth. The vast majority of the cases (92.7%) showed no response. The vast majority of the cases (92.7%) showed no improvement in pain symptoms following dental extraction. Only 4 cases showed moderate response to dental extraction. Mild response was not reported in this sample. There was no statistically significant relationship between the diagnosis and the number of extractions. Also, no statistically significant relationship between the diagnosis and the patient’s role in the extraction decision.Conclusion: There is obvious misdiagnosis leading to a considerable number of unnecessary, and multiple dental extractions for patients with TN. A considerable percentage of which is requested by patients. This reflects poor dental management of oro-facial pain. Dental education programs on both undergraduate and postgraduate levels need to focus on diagnostic defects in facial pain. These findings underscore the need for improved diagnostic training for dental professionals to prevent unnecessary invasive procedures in TN patients.Keywords: dental extraction, trigeminal neuralgia, facial pain, dental education